AGRARIAN REFORM AS A NATIONALISM ISSUE FROM COLONIAL TO REFORMASI ERA (History Department, Semarang State University and Historian Society of Indonesia, 2019)
Agrarian reform has always been regarded as a communism-related issue in Indonesia as it is often associated with the one-side action BTI (Indonesian Farmers' Union)/ PKI (Indonesian Communist Party) in the first mid of 1960s. The stigma is still attached to this present time. Whereas, agrarian reform is actually a policy that relates with various ideologies to reach different objectives. The step to conduct agrarian reform has been started since 1926 when Perhimpunan Indonesia (PI) or Indonesian Association, an organization led by Mohammad Hatta in the Netherland created the land restructured program as a part of Indonesian independence plan. In 1948, Mohammad Hatta as the Prime Minister prepared a draft of National Agrarian Law. The target was only then achieved 12 years later through the legalization of the Principal Law of Agrarian of 1960. This study employed a historical comparative study to explore the agrarian reform in Indonesia postcolonial country as a nationalism-related issue used to strengthen the national sovereignty and to improve the life of the citizens.Keyword: agrarian reform, nationalism, colonialism, post-colonial era.Â Reformasi agraria selalu dianggap sebagai masalah yang berkaitan dengan komunisme di Indonesia karena sering dikaitkan dengan aksi satu sisi BTI (Barisan Tani Indonesia) / PKI (Partai Komunis Indonesia) pada per-tengahan 1960-an. Stigma masih melekat pada saat ini. Padahal, reforma agraria sebenarnya adalah kebijakan yang berkaitan dengan berbagai ideologi untuk mencapai tujuan yang berbeda. Langkah untuk melakukan reformasi agraria telah dimulai sejak 1926 ketika Perhimpunan Indonesia (PI), sebuah organisasi yang dipimpin oleh Mohammad Hatta di Belanda menciptakan program restrukturisasi tanah sebagai bagian dari rencana kemerdekaan Indonesia. Pada tahun 1948, Mohammad Hatta sebagai Perdana Menteri menyiapkan rancangan UU Agraria Nasional. Target tersebut baru tercapai 12 tahun kemudian melalui legalisasi Undang-Undang Pokok Agraria tahun 1960. Studi ini menggunakan studi perbandingan historis untuk mengeksplorasi reformasi agraria di Indonesia pascakolonial sebagai isu terkait nasionalisme yang digunakan untuk memperkuat kedaulatan nasional dan untuk meningkatkan kehidupan warga.Kata kunci: reformasi agraria, nasionalisme, kolonialisme, era pasca-kolonial.Â Â